Normative realities of the juridical person as civil responsible third in the Cuban criminal process - Leaned Matos Hidalgo (Revista Brasileira de Direito Processual Penal)
This article carries out a study about the possibilities of the juridical person's intervention as civil responsible third in the criminal process, because in the process of upgrade of the economic Cuban pattern, this fellow is fundamental in the management and economic development of the country, because several breaches of the artificial person's civil impunity exist, for crimes made by their agents, officials, directive and workers in the exercise of their functions. In this sense they are made coincide the responsibilities civilian incorrectly and penal with the natural responsible person penal, aspects that are discussed in the investigation that shows up, because it is of vital importance the upgrade of the norms that allow the victim to obtain a direct, sure and quick compensation for effects of the penal justice. The methods analysis and synthesis are used, historical-logical, juridical, theoretical juridical exegetic and juridical compared analysis.